FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA PEMERINTAHAN DAERAH KALIMANTAN BARAT - Endang Kristiawati (Akuntabilitas, 2015)
This study aims to determine what factors are instrumental in the successfulimplementation of accrual based accounting in the Environment Government of WestKalimantan Province. This type of research is case study based on the model Luder (1992),using a qualitative approach. Study sites in West Kalimantan regional administration,sample’s in this study are SKPD-SKPD in regional government of West Kalimantan Province.Data collection techniques using observation, indepth interview, and documentation. Dataanalysis using data reduction, presentation of data and drawing conclusions / verification.,the technique checks the validity of the data using the method of triangulation. The analysisof this study suggest that in general local government officials in West Kalimantanenvironment to understand what was essentially based on accrual accounting system,although not yet fully understood. From the findings and analysis of data, there are severalfactors that are most instrumental in the successful implementation of accrual accounting ingovernment of West Kalimantan, namely commitment, quality human resources required,and Tool SupportDOI: 10.15408/akt.v8i3.2771